The relevance of identifying the biomechanical and functional effects of abdominar obesity on activities of daily living in individuals with low back pain - Anastasiia Nahorna; Heiner Baur (Bern Open Publishing, 2023)
The Global Burden of Disease Studies 2019 defines low back pain (LBP) as pain in the area of the posterior aspect of the body from the lower margin of the twelfth rib to the lower gluteal folds with or without pain referred into one or both lower limbs that lasts for at least one day. Disability due to LBP increased by more than 50% since 1990 and this disability holds the first place in years of healthy life lost due to disability (YLD) which is reflected by medical, insurance and pension statistics of the countries of the civilized world (GBD 2019 Diseases and Injuries Collaborators, 2019). It has been established that a high body mass index is one of the main risk factors for LBP (Shiri et al., 2010). A number of studies demonstrating a significant association between LBP development and abdominal obesity. Based on the findings of these studies, it is concluded that abdominal obesity is an independent risk factor for LBP (Uçar et al., 2021). However, there are only a few studies on the musculoskeletal characteristics developed as a result of this association. Existing knowledge on the identification and explanation of biomechanical role of abdominal obesity in the development of LBP, description and evaluation of the movement patterns of people with LBP and abdominal obesity and comparing their characteristics to the movement patterns of healthy adults needs to be supplemented by new data. A study is proposed that investigates postural control and (neuro-) biomechanical movement patterns during various daily basic and complex movements in adults with abdominal obesity and LBP will qualitatively extend existing recommendations for LBP therapy. The investigation of central obesity-related postural alterations and compensatory mechanisms/strategies during activities of daily living compared to individuals without central obesity and exploring possible associations between those biomechanical alterations and body composition are relevant. In the concept of a "personalized medicine" approach, these individualized recommendations are needed to be added to comprehensive current patient-oriented strategies of obesity management for people with LBP. Such data and additional recommendations are also needed for the development of current methods of obesity management in order to properly and effectively organize physical exercise for people with LBP. References GBD 2019 Diseases and Injuries Collaborators. (2019). Global burden of 369 diseases and injuries in 204 countries and territories, 1990-2019: A systematic analysis for the Global Burden of Disease Study. Global Health Metrics. The Lancet, 396(10258), 1204-. 1222. https://doi.org/10.1016/S0140-6736(20)30925-9 Shiri, R., Karppinen, J., Leino-Arjas, P., Solovieva, S., & Viikari-Juntura, E. (2010). The association between obesity and low back pain: A meta-analysis. American Journal of Epidemiology, 171(2), 135-154. https://doi.org/10.1093/aje/kwp356 Uçar, İ., Karartı, C., Cüce, İ., Veziroğlu, E., Özüdoğru, A., Koçak, F. A., & Dadalı, Y. (2021). The relationship between muscle size, obesity, body fat ratio, pain and disability in individuals with and without nonspecific low back pain. Clinical Anatomy, 34(8), 1201-1207. https://doi.org/10.1002/ca.23776